Erratum: Abstracts from the 8th International Congress of the Asia Pacific Society of Infection Control (APSIC). [Antimicrobial Resistance and Infection Control. 6, 2 (2017)(25)] DOI: 10.1186/s13756-017-0176-1 - Teresa Conceição (2018)
© The Author(s). After publication of this supplement abstract article [1], some errors in the published version [1] were reported and are included in this erratum. Abstract PM4 was accidentally withdrawn during the processing of the supplement when it should not have been. The Publisher apologises for this error and inconveniences caused. PM4 has been included in full this erratum. In the abstract AR11, "3 MRGN" and "4 MRGN" were incorrectly included as "MGRN" in the 'Material and methods' section. This has been corrected in the abstract in this erratum. In abstract AR12, "95% CI" was incorrectly referred to as "95% C.I". A point should not have been included between "C" and "I". This has been corrected in the abstract included in this erratum. In abstract E6, "aims" was incorrectly indicated as "aim" and "of the study is" should not have been included in the 'Background' section. These have been corrected in the abstract in this erratum. In the abstract PM1, "Kirby-Bauer" was incorrectly referred to as "Kirby-bauer" in the 'Materials and methods' section. The correct presentation of this is included in the abstract in this erratum. In abstract PM6, "pathogens" and "vancomycin" were capitalised incorrectly in the 'Background' and 'Materials and methods' section. These have been corrected in the abstract in this erratum. In abstract PM12, Nattawipa Boonkirdram's Family Name was incorrectly presented as "boon kirdram". This has been corrected in the abstract in this erratum.